Investigating the aphid resistance mechanisms in Triticum monococcum (L.) - Borg, Alexander (2024)
Aphid resistance against Rhopalosiphum padi and Sitobion avenae in modern wheat is lacking with current aphid control measures relying on the use of insecticides. The current way of insecticide use is unsustainable and new approaches are needed to control aphid pests. Previous studies have identified Triticum monoccocum accessions MDR045 and MDR049 showing promising signs of resistance against both R. padi and S. avenae, however, the mechanisms involved in their resistance remain elusive. The aim of this project is to further characterise the aphid resistance mechanisms in MDR045 and MDR049, focusing on the role of the plant’s secondary metabolites (SMs).